Sustainability Level of Heritage Cities in Malaysia - Yazid Saleh; Hanifah Mahat; Mohmadisa Hashim; Nasir Nayan; Samsudin Suhaily; Mohamad Khairul Anuar Ghazali (Forum Geografi, 2022)
This article aims to measure the level of sustainability of heritage cities in Malaysia. A thousand residents of ten selected heritage cities throughout Malaysia were selected as the respondents based on the cluster sampling and simple random methods to complete the questionnaire. A Likert scale on questionnaires 1 to 5 was used to elicit feedback. Five sustainability constructs were used: economic, social, environmental, cultural heritage, and government/community role. The results showed that the items in each study construct achieved an acceptable reliability level, with a Cronbach Alpha value greater than 0.70, and also met the normality test requirements. Descriptive analyses of the frequencies, percentages, and average mean values were used to establish each construct's level of sustainability. The results of the study show that the cities that attracted high scores were Georgetown (3.94), Taiping (4.00), Melaka City (3.76), and Muar (3.71). Meanwhile, the cities that attracted moderate scores were Kuala Kubu Bharu (3.36), Jugra (3.23), Tampin (3.37), Kuala Lipis (3.28), Kota Bharu (3.65) and Kuching (3.51). The implications of this study can be used to indicate the actual situation of the level of sustainability of heritage cities and be a reference to carry out the process of improvement towards a more sustainable city by 2030.